ANALISIS TINGKAT KESULITAN (DIFFICULTY LEVEL) SOAL PADA BUKU SEJARAH KEBUDAYAAN ISLAM KURIKULUM 2013 - R Ahmad Nur Kholis (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2017)
This study aims to describe the proportion of problem difficulty levels presented in chapters 1 and 2 of the Teachers' Book of Curriculum 2013 of Islamic Culture History Subject (SKI) published by the Ministry of Religious Affairs in 2015. The data analyzed in this study is a matter of discussionon: (1 ) Traces of Abbasid Abbasid Civilizations; and (2) The Brilliance of Muslim Scientists of the Abbasid Dynasty. Analytical techniques used in this study there are 2 (two), namely: (1) Descriptive statistical analysis or also called social statistics; (2) The technique of proportional analysis respondscorrectly in the analysis of difficulty level (difficulty level). The result of the analysis shows that the problems in the two sections of the book are presented in proportion: (1) 25% of the questions in the easy category; (2) 35% matter in medium category; and (3) 40% problem in difficult category(difficult). Thus, it can be concluded that these problems can be said to be ideal as a matter of practice.